2002
DOI: 10.1051/0004-6361:20020486
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of four early-type eclipsing binaries

Abstract: Abstract. New spectroscopic data were obtained for the early-type binaries V337 Aql, V649 Cas, V382 Cyg, and V431 Pup. Their radial velocity curves are presented. These are the first such data for V337 Aql and V431 Pup. In the case of V382 Cyg, our data confirm previously obtained results. Especially for V649 Cas our radial velocity curve yields important new implications for the component masses: the detection of third body lines, which are blended with the lines of the primary component, solves the problem o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 24 publications
1
28
1
Order By: Relevance
“…Column 3 of Table 2 lists the period values obtained. Their weighted mean is P = 5.816032 ± 0.000058 days, which is very close to the He i λ4471 value and contains both ST96 and Mayer et al (1992) values within a ±1σ interval. The very small uncertainty of the ST96 period determination results from the large time base of their IUE data set (∼5860 days) which is almost exactly four times ours.…”
Section: The Periodsupporting
confidence: 52%
See 2 more Smart Citations
“…Column 3 of Table 2 lists the period values obtained. Their weighted mean is P = 5.816032 ± 0.000058 days, which is very close to the He i λ4471 value and contains both ST96 and Mayer et al (1992) values within a ±1σ interval. The very small uncertainty of the ST96 period determination results from the large time base of their IUE data set (∼5860 days) which is almost exactly four times ours.…”
Section: The Periodsupporting
confidence: 52%
“…The study of the light curve of HD 152248 by Mayer et al (1992) revealed that the system displays two eclipses of unequal depth and that both minima are not separated by a 0.5 cycle, suggesting a non-zero eccentricity. Based on IUE observations and using a cross-correlation technique, Stickland et al (1996, ST96 hereafter) derived a period of 5.816083 days, an eccentricity of 0.124 and a mass ratio of 0.941.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra are listed in Table 1. They were reduced with the MIDAS package; details of the reduction procedure were described by Mayer et al (1997). The S/N ratio of the ECHELEC spectra is about 150, in case of CAT/CES spectra about 250.…”
Section: Spectroscopymentioning
confidence: 99%
“…HD 75821 (#4) : this eclipsing binary has a period of about 26.3 days and a radial velocity semi-amplitude of 92 km s −1 (Mayer et al 1997).…”
Section: Spectroscopic Binariesmentioning
confidence: 99%